Increasing profit of Arigato-O through reduction of costs due to shortage and excess of supply of takoyaki using newsboy model - Bracamonte, Rameses Isaac M.; Navarro, Don Paolo S. (Quezon City College of Engineering, University of the Philippines Diliman, 2016)
Many small businesses today struggle in not only maintaining inventory but also in estimating the needed inventory the next day to satisfy demand. Arigato-O Ja-Pi Food House, a small Japanese-Filipino food store that serves mix of delicacies, is popular because of its takoyaki. Currently, the store makes a steady profit but the management is worried as it still experiences stockouts and many times, excess stocks. Given that the store operates on single-period inventory, it is essential that its stocking level is at its optimum. It was found out that in a period of three months, they faced stockouts 6.59% of the time and 93.41% are when they are in excess. The objective was to increase profit and to decrease cost of shortage and excess at the same time by finding the optimal stocking level using Newsboy Model. It was found out that the required service level of Arigato-O's. Takoyaki batter is 64.20%. Consequently, optimal stocking levels for weekdays and weekends were found to be 53 and 71 respectively. Using these stocking levels will increase profit by 16.55% which exceeded the desirable increase of 15%.
Submitted in partial fulfillment of the course requirements in IE 151 : Production systems.
Keywords: Food industry and trade -- Production control; Cost control; Inventory shortages; Newsboy; Service level